PELATIHAN BINCANG NUMERASI DALAM MENUMBUHKAN BUDAYA BERNALAR MATEMATIKA SISWA SMK NEGERI 1 DENPASAR PADA KEHIDUPAN SEHARI-HARI - I Dewa Putu Juwana; I Dewa Gede Aditya Satria Wibawa; I Komang Sukendra; Ni Made Pira Erawati (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2026)
This community service activity aims to foster a culture of mathematical reasoning in students through numeracy discussion training at SMK Negeri 1 Denpasar. The problems encountered include students' low numeracy skills in daily life, low reading interest and understanding of numeracy concepts, and limited numeracy learning resources used by teachers. The activity was implemented through five stages: outreach, training, technology implementation, mentoring and evaluation, and program sustainability. The training was conducted through interactive discussions, the use of everyday life contexts, digital media, and the application of the STAR method in the numeracy discussion activities. The results showed that the numeracy discussion training increased student participation in discussions, fostered numeracy skills, and enhanced students' ability to understand and apply numeracy concepts to real-world situations. Furthermore, teachers gained new insights into utilizing more varied, contextual, and innovative numeracy learning resources. Thus, numeracy discussion training can be an effective strategy for strengthening numeracy culture and students' critical thinking skills in schools.